Prevalence of Black Stain and Dental Caries in Children Attending a University Pediatric Dentistry Clinic in Istanbul - AKYÜZ, SERAP HATİCE (AVES PRESS LTD, 2015)
Objective: The purpose of the present study is to investigate the prevalence of black stain and dental caries in Istanbul schoolchildren attending a university pediatric dentistry clinic and compare it with the literature findings from other countries. Methods: Presence of black stain and WHO df-t/DMF-T scores were recorded from randomly selected 325 (boys: 167, girls: 158) schoolchildren between 5 to 13 years of age who reside in Istanbul and attend Marmara University Pediatric Dentistry Clinic. Results: Black stain was observed in 60 children (27 boys, 33 girls). The overall percentage of children affected by black stain was 18.5%. The mean df-t, DMF-T scores for children with black stain (3.67 +/- 3.25; 1.39 +/- 1.68) did not differ from children without black stain (4.29 +/- 3.48; 1.79 +/- 2) (p>0.05). Number of children with and without black stain did not differ according to DMF-T and df-t scores, gender, parental education levels and toothbrushing frequency (p>0.05). Conclusions: The mean df-t and DMF-T scores were not statistically different between the groups with stain and without stain. Black staining and df-t, DMF-T scores were not associated with each other. The prevalence of staining in our sample was found higher than the prevalence reported from Brazil, Italy, Germany, Spain, Poland, Philippines, India, Greece, and China but lower than those reported from Switzerland and United Kingdom.
Keywords: Black stain; dental caries; children